Mixing Time, Inversion and Multiple Emulsion Formation in a Limonene and Water Pickering Emulsion - Sawiak, Laura; Bailes, Katherine; Harbottle, David; Clegg, Paul S. (Frontiers in Chemistry, 2018)
It has previously been demonstrated that particle-stabilized emulsions comprised of limonene, water and fumed silica particles exhibit complex emulsification behavior as a function of composition and the duration of the emulsification step. Most notably the system can invert from being oil-continuous to being water-continuous under prolonged mixing. Here we investigate this phenomenon experimentally for the regime where water is the majority liquid. We prepare samples using a range of different emulsification times and we examine the final properties in bulk and via confocal microscopy. We use the images to quantitatively track the sizes of droplets and clusters of particles. We find that a dense emulsion of water droplets forms initially which is transformed, in time, into a water-in-oil-in-water multiple emulsion with concomitant changes in droplet and cluster sizes. In parallel we carry out rheological studies of water-in-limonene emulsions using different concentrations of fumed silica particles. We unite our observations to propose a mechanism for inversion based on the changes in flow properties and the availability of particles during emulsification.